Investigation of Reactive Red 198 Dye Removal by Chitosan from Aqueous Solution - Carbaş, Hamiyet Ö.; Kadak, Ali E.; Küçükgülmez, Aygül; Gülnaz, Osman; Çelik, Mehmet (SAABRON PRESS, 2023)
This study used chitosan, a biopolymer with high adsorption capacity obtained from shrimp shells, to remove Reactive Red 198 dye from water. The effects of pH, temperature, dye concentration, and particle size on adsorption were investigated. The optimum pH level for the adsorption was determined as 5. The effect of the temperature was found to be adverse, and it was observed that the adsorption capacity of chitosan decreases as the temperature increases. Considering the effect of the initial dye concentration, the adsorption values of under-size chitosan (passed through a 150-mesh sieve) and over-size chitosan (retained on a 150-mesh sieve) at 200 mg/L dye concentration were 197.38 and 196.22 mg/g, respectively. At 100 mg/L dye concentration, these values were 97.41 and 96.10 mg/g, respectively. Adhesion of the Reactive Red 198 was easier because the adsorption surface area expanded with the reduction of the particle size of the chitosan. According to the results of the study, it was seen that the isotherm model of adsorption is a suitable monolayer for the Langmuir isotherm model. Langmuir isotherm’s maximum adsorption capacity (Qmax) was calculated as 500 mg/g. The kinetic model was in line with the pseudo-second-order kinetic model. The FTIR spectra of the chitosan before and after adsorption showed that the adsorption is indeed chemical. Furthermore, SEM results demonstrated that the adsorption was more efficient due to the fibrous and porous structure of the chitosan.
Keywords: shrimp chitosan; adsorption from aqueous solution; RR 198; dye removal